2022
DOI: 10.34172/jcs.2022.037
|View full text |Cite
|
Sign up to set email alerts
|

Concept Analysis of End-of-Life Care

Abstract: Introduction: The inevitability of human mortality encourages the care system to enhance the Quality of Life (QOL) at the end of life. However, the main problem is that the boundaries of care as End-of-Life care (EOLC) have not been defined precisely. Hence, this study aimed to clarify the concept of EOLC. Methods: This study was conducted based on Walker and Avant's eight-step approach (2019). A detailed review of the literature was accomplished in the databases including PubMed/Medline, Web of Sciences, Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…13 In addition to clarifying ambiguous and confusing concepts, concept analysis can clarify commonly-used concepts, distinguish a concept from similar ones, and provide a basis for concept development. 11 , 14 …”
Section: Resultsmentioning
confidence: 99%
“…13 In addition to clarifying ambiguous and confusing concepts, concept analysis can clarify commonly-used concepts, distinguish a concept from similar ones, and provide a basis for concept development. 11 , 14 …”
Section: Resultsmentioning
confidence: 99%
“…This choice may have stemmed from a reluctance to verbalise deeply personal matters or a desire to maintain control over their vulnerability [ 52 ]. Respecting patients’ decisions regarding communication was crucial in these instances, as part of a person-centred approach [ 10 ]. The realisation of limited time and the uncertainty of when death would occur led patients to attempt to navigate the situation through different strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A central approach involves communication and interaction between patients and nurses, grounded in patients’ beliefs, needs, stories, thoughts and feelings [ 8 , 9 ]. A person-centred approach may ensure holistic care by nurses to patients with palliative care needs [ 10 ]. Conversation between patients and nurses is anything but superficial; it is complex, effective, and confidential, offering important potential for interaction and emotional support [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experts have concluded that knowledge of aesthetics is essential for nurses to achieve high levels of EoL care perception [ 14 ]. It is because EoL care is linked with certain characteristics to which nurses need to attend, including a proper understanding of creativity and purposefulness, skills, relationships, totalitarianism, personalization of care, application of empirical knowledge, and adherence to ethical principles [ 15 ].…”
Section: Introductionmentioning
confidence: 99%